Implementation Of Local Food Supplements On Weight Gain Of Pregnant Women Chronic Energy Deficiency Of Indigenous Papuans At Mopah Baru Health Center - Suhartini, Suhartini; Retnaningtyas, Erma; Suharto, Hans Angelius; Muslichah, Miftakhul (Journal of Midwifery and Nursing, 2025)
One of the efforts to prevent the impact of Chronic Energy Deficiency in Pregnant Women is by providing additional food. This study aims to determine the Implementation of Providing Supplementary Food Made from Local Food on Weight Gain in Pregnant Women with Chronic Energy Deficiency of Indigenous Papuans at the Mopah Baru Health Center. The study design was Observational Analytical cross sectional. A sample of 30 pregnant women with Total sampling technique with Chi Square statistical test. Independent variables (Provision of Supplementary Food) and dependent variables (Weight Gain) using observation sheets. The results of the study were obtained from 30 respondents, who finished the Supplementary Food  made from local food well, namely 19 respondents (63.3%), and those who experienced an increase in Body Weight were 16 respondents (53.3%). There is a relationship between the Provision of Supplementary Food . Made from Local Food on Weight Gain in Pregnant Women with Chronic Energy Deficiency of Indigenous Papuans  with p value = 0.000 <0.05. Pregnant women with chronic energy deficiency need to pay attention to their diet and nutritional intake during pregnancy and the need for midwives to play a role in implementing the provision of additional food made from local food from the government